Minat Beli Green Cosmetics Halal Generasi Milenial: Peran Green Trust dan Customer Engagement - Bunda, Cici Aulia Permata; Faqihuddin, Faqihuddin; Jatnika, Muhammad Dzulfaqori (ITB AAS INDONESIA Surakarta, 2024)
This study aims to describe the purchasing behavior of halal and environmentally friendly cosmetics among Muslim millennials. The concepts of green marketing and theory of planned behavior are combined to see their influence on interest in using halal green cosmetics. Respondents in this study were 350 Muslim millennials who live in West Java Province. The questionnaire was distributed using non-probability convenience sampling. Hypothesis testing in this study used the Structural Equation Model Partial Least Square approach. The results of this study are green perceived value, green perceived risk, attitude towards green purchasing, brand experience, and customer engagement have both direct and indirect effects. This research only covers the people of West Java Province, in the future samples can be added that cover all of Indonesia or between countries.